1997
DOI: 10.1088/0953-4075/30/4/021
|View full text |Cite
|
Sign up to set email alerts
|

Electron impact excitation of magnesium and zinc atoms in the relativistic distorted-wave approximation

Abstract: A calculation based on a relativistic distorted-wave approximation has been carried out for the electron impact excitation of the 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 31 publications
3
48
1
Order By: Relevance
“…The linear polarizations from that study were well reproduced by both the CCC (Fursa and Bray 2001) and RMPS methods. The relativistic distorted-wave (RDW) method of Kaur et al (1997) and the first-order many-body theory (FOMBT) of Meneses et al (1990) also showed substantial agreement with experiment. It might be expected that distorted-wave methods would work well at this energy of almost ten times the excitation threshold.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…The linear polarizations from that study were well reproduced by both the CCC (Fursa and Bray 2001) and RMPS methods. The relativistic distorted-wave (RDW) method of Kaur et al (1997) and the first-order many-body theory (FOMBT) of Meneses et al (1990) also showed substantial agreement with experiment. It might be expected that distorted-wave methods would work well at this energy of almost ten times the excitation threshold.…”
Section: Introductionmentioning
confidence: 71%
“…The present CCC and RMPS calculations are in excellent agreement with each other Figure 2. Differential cross sections for elastic scattering and excitation of the 3 1 P and 3 3 P states of magnesium at 20 eV: (•) present data; ( ) Brunger et al (1989) (3 1 P), Houghton et al (1994) (3 3 P); (×) Williams and Trajmar (1978) Mitroy and McCarthy (1989); (---) FOMBT (Meneses et al 1990); (----) RDW (Kaur et al 1997).…”
Section: Differential Cross Sectionsmentioning
confidence: 94%
See 1 more Smart Citation
“…For the L± parameter the agreement between the experiment, present CCC, RDWA [8,9], and DWA [16,14,17], and calculations are very good in the forward scattering region for Mg, Ca, and Sr but not for Ba where large differences between theoretical results are apparent. At intermediate scattering angles the CCC method is in a good agreement with experiment for Mg, Ca, and Ba but for Sr we found a large discrepancy at around 50° with the DWA and RDWA results supporting the experiment.…”
Section: Resultsmentioning
confidence: 50%
“…1 and 2 for Mg (40 eV), Ca (45eV), Sr (30.3 eV), and Ba (20 eV). The results of the RDWA calculations [8,9] and experimental data indicate that relativistic effects are not important for these transitions, since both find that P + is approximately unity.…”
Section: Resultsmentioning
confidence: 92%